Profit over People? Evaluating Morality on the Front Line during the COVID-19 Crisis: A Front-Line Service Manager's Confession and Regrets. (April 2021) - Hadjisolomou, Anastasios; Simone, Sam
This article gives voice to a front-line manager in food retailing, discussing her experiences during the COVID-19 outbreak which, overnight, became an 'essential service', leaving employees exposed to the virus. The article utilizes the 'moral economy' framework to understand how organizational policies, which were developed by senior management and implemented by front-line managers, denied human flourishing and well-being during a period of socio-economic crisis. The article captures the complexity of morality in organizations across managerial levels. Questioning the morality of managerial decisions during the pandemic and emphasizing how these are driven by the intense competition in the market, it reveals that front-line managers are caught between conflicting moral values and expectations. This study contributes to the 'moral economy' framework suggesting that the structural constraints of front-line managerial authority have challenged their moral values and narrowed the space for safe and meaningful work and well-being for front-line managers and employees.